Effect of composite coatings on surface characteristics and boiling heat transfer performance in a pool of water - Kumar N.; Ghosh P.; Shukla P. (My University, 2025)
Boiling is known as an effective mode of heat transfer at low-temperature differences, due to the rapid vaporization of liquid. The performance of boiling heat transfer can be enhanced by reducing surface wettability and modifying surface structures. In this study, polished copper (bare) substrates were modified by composite coatings of TiO2 and SiO2 nanoparticles. Four different samples were prepared using electrophoretic deposition and by varying the coating duration to 5, 10, 15, and 20 min, which were named S5, S10, S15, and S20, respectively. The surface characteristics of bare and coated samples, such as morphology, wettability, surface roughness, and coating layer thickness, were investigated. The contact angle measurements of the bare surface were 65.7°, whereas the coated samples S5, S10, S15, and S20 were 112.9°, 103.6°, 100.3°, and 96.8°, respectively. The coating layer thickness of the samples S5, S10, S15, and S20 was 2.46, 4.76, 9.86, and 14.58 microns, respectively. The pool boiling performance was examined in demineralized (Milli-Q) water on bare and coated surfaces. The onset of nucleate boiling (ONB) temperature was reduced for all composite coated surfaces. The largest reduction in ONB was observed for S15, which was ~ 3.5 °C less than the bare surface. The maximum enhancements in the boiling heat transfer coefficient (BHTC) recorded for S10 and S15 were 38% and 62%, respectively. The optimum coating layer thickness was observed to be ~ 10 µm, up to which heat transfer performance was improved. © 2023, Akadémiai Kiadó, Budapest, Hungary.